Hybrid-seed production in cytoplasmic male-sterile lines of upland cotton (Gossypium hirsutum) through insect pollination - AVTAR, R; CHHABRA, B S; LATHER, B P S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during rainy season of 1991 to study hybrid-seed production in 3 cytoplasmic-genic male-sterile lines of upland cotton (Gossypium hirsulum L.) by natural (insect) pollination. The study revealed the success of insect pollination, that the pollen from restorer (R) lines to male-sterile (A) lines were transferred by a number of cotton insects visiting the flowers frequently. Male-sterile lind restorer lines grown in 2: 1 ratio showed the highest recovery of hybrid seed/ha Bolls/plant, boll weight, seeds/boll and F1-seed recovery/plant obtained after insect pollination were highest in 1 : 1 and the lowest in 4: 1 ratio, whereas reverse Was true for seed index.